The cod mating system and the risk of genetic introgression from farmed escapees - Skjaeraasen, J E; Meager, J J; Karlsen, Ø; Lokkeborg, S; Michalsen, K; Mayer, J A; Hutchings, J A; Kleven, O; Ferno, A (2007)
Most farmed Atlantic cod (Gadus morhua) in Norway are produced in net-pens in sheltered coastal areas also used by wild coastal cod. As future expansion of the industry is expected, interactions between farmed escapees and local coastal stocks are inevitable. Genetic introgression from escapees has caused fitness depression in wild Atlantic salmon (Salmo salar) populations and similar effects may occur with cod. Wild coastal cod are currently subjected to over-exploitation and are at low population size throughout their range. It is, therefore, very important to examine the potential effect cod farming and escapees may have on wild stocks. The cod mating shoal has been described as a lek which is an aggregated male display that females attend primarily for fertilisation. During spawning, males act aggressively towards each other and court females, using a combination of acoustic and behavioural displays. These behavioural interactions are directly correlated with male reproductive success. Behavioural divergence between farmed and wild populations may, therefore, limit the potential for hybridisation between them. Domestication may also influence the reproductive success of cod by affecting the development and expression of secondary sexual characteristics. We will present data from studies that tested for differences in both the morphology and the spawning behaviour of farmed and wild cod within mixed spawning shoals.